Open-book vs. closed-book examination in trigonometry: Effects on student's achievement and attitude towards mathematics - Nataya, Amparo I. (Animo Repository, 2001)
This experimental study compares the effects of the open-book and closed-book examinations in Trigonometry on the achievement and attitude of students.The study was conducted at the Cavite State University (CvSU) during the second semester of school year 2000-2001. The subjects of the study were sixty-three first year college students pursuing BS Chemistry and BS Applied Mathematics. There were two sets of achievement tests used in the study. The first set was given To BS Chemistry students who were exposed to the open-book examinations and to BS Applied Mathematics who were exposed to the closed-book examinations. The second set was administered to BS Applied Mathematics students who were exposed to the open-book examinations and to BS Chemistry students who were exposed to the closed-book examinations. The Mathematics Attitude Scale was given as pretest during the first phase of the experiment. On the last day of the experiment in Phase 1, the same test was given as posttest. The students were classified into above average and below average using their final grades in Math 11 (College Algebra).The two-factor analysis of covariance (ANCOVA) was used to test the significance of the achievement and attitude change of students toward mathematics. The t-test for independent samples was used to determine whether a significant difference exists between the scores of the students who took the open-book and closed-book examinations. A comparison of the post-experimental attitude scores of the Experimental group and the Control group was done with the use of t-test for individual samples. Possible significant differences in the attitude of each group towards mathematics before and after the experiment were tested using the t-test for dependent samples. The null hypotheses were all tested at 0.05 level of significance. The findings revealed the following: (1) in Phase 1, the Control group with closed-book examinations achieved higher than the Experimental group with open-book examinations, while in Phase 2, the Experimental group with open-book examinations achieved higher than the Control group with closed-book examinations (2) the attitude towards mathematics of students who underwent open-book examinations and a closed-book examinations did not differ significantly (3) there was no interaction between the testing methods and mental ability levels on students' achievement in Trigonometry.Based on the results of the study it was concluded that open-book examinations in Trigonometry was not significant on the achievement of the students due to teacher factor effect, mathematical abilities and background of the students and the subject matter.